Active packaging systems based on metal and metal oxide nanoparticles - Ballesteros, Lina F. (2021)
Summary Active packaging refers to a set of systems usually aiming to protect and extend the shelf life of food. The incorporation of metal (e.g. zinc, silver, copper, and gold) and metal oxide (e.g. zinc oxide, titanium dioxide, and magnesium oxide) nanoparticles into petroleum-based and bio-based polymers has progressively increased for active packaging purposes. These nanoparticles provide to the packaging functional characteristics such as antimicrobial capacity, oxygen scavenging, and photocatalytic activity, as well as better mechanical performance and enhancement of barrier properties. Therefore, the present chapter overviews the incorporation of metal and metal oxide nanoparticles into different materials for the development of active packaging systems with multiple functionalities. The types of metal nanoparticles applied to package materials, the main production methods, and the incorporation of them into the packaging are addressed. Additionally, the main features and limitations related to the effect of metal-based nanoparticles on the packaging properties, as well as the possible particle migration to the food and environment when discarded, are discussed.